-3(-2x-4)-5=(x-1)=5x

Simple and best practice solution for -3(-2x-4)-5=(x-1)=5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-2x-4)-5=(x-1)=5x equation:



-3(-2x-4)-5=(x-1)=5x
We move all terms to the left:
-3(-2x-4)-5-((x-1))=0
We multiply parentheses
6x-((x-1))+12-5=0
We calculate terms in parentheses: -((x-1)), so:
(x-1)
We get rid of parentheses
x-1
Back to the equation:
-(x-1)
We add all the numbers together, and all the variables
6x-(x-1)+7=0
We get rid of parentheses
6x-x+1+7=0
We add all the numbers together, and all the variables
5x+8=0
We move all terms containing x to the left, all other terms to the right
5x=-8
x=-8/5
x=-1+3/5

See similar equations:

| 21.99=4g+3.95 | | 6=1-n2+5 | | 3(r-10)=90+9r | | -4-x=-26 | | 6b+25=4b-13 | | (2y–3)=29 | | 5x+3=(x-3)2 | | 4x-(x+3)=8 | | 2.2=z➗57 | | 120-3x+3x+25=180 | | 4/5+y=1/7 | | V–x+F=2 | | N=735/n | | 4x-10=6x+-2 | | 5x^2=37x+24=0 | | 2y–3=29 | | -8-3n=-4n-5 | | 2x+9=8(3x-4) | | 19+2p=-27 | | -3x+9=-3+9 | | -y-3-2y=9 | | 2x+5=8+2x | | 7+5n=6(4n-3)+6n | | -1=5+s/6 | | 5(a+4)-6a+1=20 | | 5x+9=(3+10)+(2x-1) | | 3x+4+2x+4=48 | | 12-9j=-3j-18 | | -9h=-7-10h | | 168=2x-6 | | 17x+43x=0 | | 3(2y+7)=9 |

Equations solver categories